A cena em processo: metateatro e Viewpoints na peça Gaivota - tema para um conto curto - Cerbara, Marcella Vicentini (2015)
This research aims to contribute to the analysis of contemporary theater scene, based on the play, Gaivota tema para um conto curto, collectively building by Bel Garcia, Emilio de Mello, Enrique Diaz, Felipe Rocha, Gilberto Gawronski, Isabel Teixeira, Mariana Lima and directed by Enrique Diaz. This work focus out the main procedures used in the spectacle as the actor-performer, the technique of Viewpoints and metateatro. The classic text used as a starting point is A Gaivota, the Russian author Anton Chekhov, reference of the innovations proposed by Stanislavisky and the Moscow Art Theatre in the early twentieth century. The aim is to keep registered one of the trendiest of today: the reading of dramatic texts